A Brief Review on the Synthesis of Zeolites from Hazardous Wastes. Issue 1 (2nd January 2017) - Mallapur, Veeresh P.; Oubagaranadin, John U. Kennedy
ABSTRACT: Zeolite is a versatile and environmentally important micro-porous material which can be synthesized using inorganic wastes like fly ash, porcelain wastes, natural clays, rice husk ash and also from its chemical precursors. Silica and alumina are the source materials for the synthesis of zeolites. Various industries produce hazardous inorganic wastes that are rich in silica and alumina, and its production rate worldwide is enormous. Majority of these wastes are dumped in landfills and only a very small percentage is reutilized. The cost of synthesis of zeolite from inorganic waste materials is very less when compared to synthesis from its chemical precursors. Zeolite synthesis from such hazardous material has shown promising and versatile industrial applications. This paper gives an overview of zeolite synthesis from hazardous inorganic wastes such as fly ash, municipal solid wastes, waste metallic residues, lithium slag, agro wastes, porcelain wastes, waste LCD panel glass, waste kaolin from industry, windshield waste, cupola slag with aluminium sludge and waste stone cake.